2016
DOI: 10.1118/1.4940354
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of oncological 18F‐FDG PET/CT imaging based on a multiparameter analysis

Abstract: Consistent oncological PET/CT image quality on a high-performance scanner was achieved from an analysis of the relations existing between dose regimen, patient habitus, acquisition, and processing techniques. The proposed methodology may be used by PET/CT centers to develop protocols to standardize PET/CT imaging procedures and achieve better patient management and cost-effective operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Variation could also be caused by possible (unknown) liver inhomogeneities within the VOI. Nevertheless, the clarified variability is slightly lower but comparable with findings by de Groot et al [20] and Menezes et al [21]. In both 18 F-FDG studies, body mass also has the highest R 2 with respectively SNRnorm (R 2 = 0.77, Biograph mCT with OSEM3D + PSF + TOF reconstruction) and the normalized coefficient of variation (R 2 = 0.86, Biograph trueV with OSEM3D + PSF reconstruction).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Variation could also be caused by possible (unknown) liver inhomogeneities within the VOI. Nevertheless, the clarified variability is slightly lower but comparable with findings by de Groot et al [20] and Menezes et al [21]. In both 18 F-FDG studies, body mass also has the highest R 2 with respectively SNRnorm (R 2 = 0.77, Biograph mCT with OSEM3D + PSF + TOF reconstruction) and the normalized coefficient of variation (R 2 = 0.86, Biograph trueV with OSEM3D + PSF reconstruction).…”
Section: Discussionsupporting
confidence: 85%
“…This study showed that a quadratic relationship between administered activity, body mass, and acquisition time delivered a more constant PET image quality than a linear dose regimen for 18 F-FDG. Moreover, in a later study by Menezes et al [21], body mass was found as best predictor in a univariate analysis. Furthermore, a multivariate analysis in a study by Wickham et al [12] showed a combination of body mass, sex, and length as best predictors.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Despite the wide literature on optimization of PET protocols for lesion detectability (6)(7)(8)(9)15) or the impact of noise on quantitation (16)(17)(18)(19), there is still limited work optimizing low-dose PET as a quantitative biomarker using guidelines such as the EANM criteria (20,21). Advances in PET image reconstruction algorithms that incorporate PSF modeling have reduced noise and increased resolution, potentially allowing for reduced injected activity and thus lower radiation exposure to patients (15,(22)(23)(24)(25), opening new scenarios for cancer screening with PET (15,26,27).…”
mentioning
confidence: 99%